Criteria of initial selection of candidates for artistic gymnastics - Kochanowicz, K.; Kochanowicz, A. (Baltic Journal of Health and Physical Activity, 2010)
Background: The effectiveness of the training process and the level of sports results largely depend on the selection of candidates with appropriate psycho-physical predispositions and the efficiency of the training system. Therefore, selection for artistic gymnastics must be based on coaches' thorough knowledge regarding physical development, interdependence of particular systems and analysers, motor skills and mental determinants.